Implementasi Sistem Ekonomi Pancasila dalam Kebijakan Pemerintah Indonesia - Marsudi, Kenlies Era Rosalina; Purbasari, Verbena Ayuningsih (Indonesian Journal of Islamic Economics and Finance, 2022)
Pancasila economic system is a concept of thinking about the planning and implementation of the national economy with a framework based on the elaboration of the values that exist in the Pancasila paradigm. The implementation of the Pancasila economic system is crucial in view of the phenomenon of global capitalism and the COVID-19 pandemic which has resulted in decreased economic stability. The decline in economic stability in Indonesia today increasingly shows that the implementation of the Pancasila economy has deviated and is displaced by the existence of a capital-liberal economic system which has ultimately led to inequality in the people's economy. The purpose of this study is to analyze the existence of the economic implementation of Pancasila in various government policies in facing the onslaught of global capital liberalism. The research method uses literature studies, by presenting theories related to titles obtained from books, journals and online media. This research finds that the implementation of the Pancasila economic system in various government policies is still apparent. This nation has been faced with globalization and economic modernization as serious challenges in maintaining the wisdom of the nation's economic culture without having to be left behind from these world phenomena. This has become a very hard homework for the government structure in initiating Indonesian economic regulations and policies that must prioritize the people's economy. The populist economic system is a suitable solution to be applied in Indonesia which relies on Pancasila.